2009
DOI: 10.1007/s00606-009-0187-3
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Gottschelia grollei, G. patoniae and Scaphophyllum speciosum to Solenostoma based on chloroplast DNA rbcL sequences

Abstract: Maximum parsimony and Bayesian analyses of a chloroplast DNA rbcL dataset indicate a position of Gottschelia schizopleura in Scapaniaceae (Jungermanniales suborder Cephaloziineae). Gottschelia grollei, G. patoniae and Scaphophyllum speciosum are nested in Solenostoma (Solenostomataceae, Jungermanniales suborder Jungermanniideae) and are transferred to this genus. Accessions of G. schizopleura from Africa and Asia are separated by long branches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…At the time we began this study, existing molecular data were not sufficient to resolve the taxonomic affinities of Solenostoma and Plectocolea, due mainly to insufficient sampling of both taxa and DNA loci (Feldberg et al 2009;Henstchel et al 2007). Compared with our previous study (Vilnet et al 2011) here we additionally used the sequences of trnG-intron and increased the sampling for both genera: for Solenostoma from five species to ten (plus one unknown species), for Plectocolea from eight to fifteen, with multiple accessions in the most cases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…At the time we began this study, existing molecular data were not sufficient to resolve the taxonomic affinities of Solenostoma and Plectocolea, due mainly to insufficient sampling of both taxa and DNA loci (Feldberg et al 2009;Henstchel et al 2007). Compared with our previous study (Vilnet et al 2011) here we additionally used the sequences of trnG-intron and increased the sampling for both genera: for Solenostoma from five species to ten (plus one unknown species), for Plectocolea from eight to fifteen, with multiple accessions in the most cases.…”
Section: Discussionmentioning
confidence: 98%
“…The phylogenetic relationship between Plectocolea and Solenostoma was not investigated earlier and only preliminary results were known from analysis of rbcL cpDNA data (Hentschel et al 2007;Feldberg et al 2009). Hentschel et al (2007) recovered two Solenostoma species and four Plectocolea species (cited as Solenostoma) in an intermingled clade with different affinities among taxa based on MP and ML analyses.…”
mentioning
confidence: 99%
“…Based on chloroplast DNA evidence, Feldberg et al (2009) excluded Gottschelia Grolle from the Jamesonielloideae and placed its species in different suborders of the Jungermanniales. De Roo et al (2007) demonstrated the paraphyly of Jamesoniella (Spruce) F. Lees, with species of Cryptochila R.M.…”
Section: Introductionmentioning
confidence: 99%
“…Taxon sampling and assembling of DNA sequence data For this study, we obtained chloroplast DNA rbcL-and psbA-sequences of most genera that are assigned to the Cephaloziineae based on the morphological studies or on the molecular phylogenetic results of several preceding works (Forrest et al 2006;He-Nygrén et al 2006;de Roo et al 2007;Heinrichs et al 2007;Feldberg et al 2009Feldberg et al , 2010Vilnet et al 2010). In addition to a DNA dataset of Adelanthaceae s. l. (Feldberg et al 2010), we obtained rbcL and psbA sequences of related lineages via DNA sequencing or GenBank.…”
Section: Methodsmentioning
confidence: 99%